Injectable Oxygen Sensitive Chitosan Complex with High Oxygen Sensitivity and Stability to Oxidoreductants - Li, Chao (ACS Biomater Sci Eng, 2019)
Various therapeutic approaches have been developed for vascularization of diseased tissues. To quickly and accurately evaluate efficacy of a therapy, reproducible monitoring of tissue oxygen concentration changes at the same tissue location by a minimally invasive or noninvasive spectroscopic approach represents a compelling strategy. Yet this cannot be achieved by any clinically available approaches. Magnetic-resonance-based method, electron paramagnetic resonance (EPR), has the potential to accomplish the goal. However, the existing small molecule EPR probes cannot maintain a consistent concentration at the same tissue location during vascularization period to acquire a stable EPR signal, and they cannot be implanted and/or retrieved by a minimally invasive approach such as injection. Herein, a polymeric, injectable, and degradable EPR probe was developed. The probe was based on the complex of chitosan and tetrathiatriarylmethyl (TAM) radical. The probe had high oxygen sensitivity and reproducibility. It was more stable than free TAM radical when exposed to oxidoreductants that commonly appear in diseased tissues. The probe maintained EPR signal intensity for 4 weeks in vitro and in vivo without changing oxygen sensitivity. It also exhibited excellent biocompatibility. The developed TAM/chitosan complex may be used for long-term detection of tissue oxygen content during therapies.